Dynamic strategies for measuring the performance of inventory system in closed loop supply chain. (17th June 2021) - Shirazi, Babak; Ebrahimi, Elnaz; Mirzagoltabar, Hadi; Mahdavi, Iraj
Closed loop supply chains are the complicated dynamical system, which focuses on all the factors involved in the comprehensive process and seeks to adopt strategies for achieving the chain established targets. The purpose of this study is to evaluate the food supply chain performance. A system dynamic approach is applied to examine the relationships and behaviour within the closed -loop supply chain. The variables with a significant effect on system performance are identified. Then, the simulated model is analysed by sensitivity to provide a tool for managers to generate policies and business decisions which can lead to enhancing the performance of the supply chain system. The results reveal lost sale-oriented to zero also inventory cost and transferring time in the lowest state by adding an intermediary unit between segments and implementation of the recommended policy.